P092 Risk factors for obstructive sleep apnea: A scoping review of systematic reviews. (9th November 2022) - Qian, Y; Dharmage, S; Hamilton, G; Senaratna, C; Perret, J
Abstract: Introduction: The high prevalence of obstructive sleep apnea (OSA) challenges public health and health care significantly. Summarizing the evidence and identifying research gaps on risk factors for OSA could focus efforts to reduce the disease burden. Methods: We performed a scoping review to map the current evidence of OSA-related risk factors. Medline was searched systematically for systematic reviews/meta-analyses including observational and interventional studies, excluding reviews limited to paediatric populations. Results: Of 974 abstracts, 49 eligible systematic reviews were retrieved, covering six major categories of risk factors, namely demographic(n=9), lifestyle(n=9), genetic(n=11), comorbidity-related(n=10), environmental(n=2), and other(e.g., protein level, surgery, n=12). Obesity/BMI and increasing age were major risk factors for OSA, however, longitudinal obesity trajectories or weight changes were not explored. Smoking was inconsistently associated with OSA. Alcohol consistently increased OSA severity(n=5). 5-HT2A(5-hydroxy-tryptamine), tumor necrosis factor- α, and angiotensin converting enzyme activity were associated with increased risk of OSA(n=4 for each). Comorbidity-related risk factors were identified including asthma, hypothyroidism, gastroesophageal reflux disease, depression while allergic rhinitis and Parkinson's disease had null and negative effects, respectively. Menopause, ethnicity, and enlarged adenoids/tonsils are yet to be systematically synthesized. Overall, there was no review analyzing any longitudinal risk factor for OSA in the general population. Discussion: Although this review supports the potential benefit of reducing OSA and its severity from weight loss and/or quitting smoking among the general population, there is an absence of data on longitudinal risk factor trajectories, which could help guide and strengthen public health policy.